Peripheral Antinociception of a Chalcone, Flavokawin B and Possible Involvement of the Nitric Oxide/Cyclic Guanosine Monophosphate/Potassium Channels Pathway - Akhtar, Muhammad Nadeem; Mohd Nasier, Kamaldin; Azam Shah, Mohamad; Lajis, Nordin; Perimal, Enoch Kumar; Akira, Ahmad; Lee, Ming-Tatt; Israf, Daud Ahmad; Mohd Roslan, Sulaiman (MDPI - Open Access Publishing, 2013)
Previous studies have shown that systemic administration of 6'-hydroxy-2',4'-dimethoxychalcone (flavokawin B, FKB) exerts significant peripheral and central antinociceptive effects in laboratory animals. However, the mechanisms underlying these peripheral and central antinociceptive effects have yet to be elucidated. Therefore, the objective of the present study was to evaluate the participation of nitric oxide (NO)/cyclic guanosine monophosphate (cGMP)/potassium (K+) channels pathway in the peripheral antinociception induced by FKB. It was demonstrated that intraplantar (i.pl.) administration of FKB (150, 250, 375 and 500 µg/paw) resulted in dose-dependent peripheral antinociception against mechanical hyperalgesia in carrageenan-induced hyperalgesia test model in rats. The possibility of FKB having either a central or a systemic effect was excluded since administration of FKB into the right paw did not elicit antinociception in the contralateral paw. Furthermore, peripheral antinociception induced by FKB (500 µg/paw) was significantly reduced when L-arginine (25 µg/paw, i.pl.), Oxadiazolo[4,3-a]quinoxalin-1-one (ODQ; 50 µg/paw, i.pl.), glibenclamide (300 µg/paw, i.pl.), tetraethylammonium (300 µg/paw, i.pl.) and charybdotoxin (3 µg/paw, i.pl.) were injected before treatment. Taken together, our present data suggest that FKB elicits peripheral antinociception when assessed in the mechanical hyperalgesia induced by carrageenan. In addition, it was also demonstrated that this effect was mediated through interaction of the NO/cGMP/K+ channels signaling pathway.